PELATIHAN PERHITUNGAN HARGA POKOK PENJUALAN PADA UMKM DI DESA MEDALKRISNA - Laila Faturohmah, Laila Faturohmah; Purwantini, Lucky; Maysaroh Chairunnisa, Nurlaila (Universitas Islam 45 Bekasi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Medalkrisna Village play a strategic role in driving local economic growth. However, many business owners face challenges in accurately calculating the Cost of Goods Sold (COGS), which affects pricing decisions. Errors in COGS calculation can lead to suboptimal profit margins and impact business sustainability. Therefore, this community service program aims to enhance MSME owners' understanding and skills in COGS calculation through a structured and practical training program. The training methodology includes theoretical presentations on cost components in COGS, interactive discussions, case studies based on real business scenarios, and hands-on practice using participants’ business data. Training effectiveness was assessed through pre-tests and post-tests to measure improvements in participants' comprehension. The results indicated a significant increase in participants' ability to accurately and systematically calculate COGS. With improved knowledge, MSME owners can set more competitive prices and enhance their business profitability. In addition to improving technical skills, this training also raises awareness of the importance of proper financial record-keeping as a foundation for sound business decision-making. The positive impact of this initiative is expected to strengthen the competitiveness of MSMEs in Medalkrisna Village, promote community-based economic growth, and foster more sustainable enterprises. Therefore, similar training programs are recommended to be conducted regularly to support the development of more professional and independent MSMEs.